(2x/7)-7=-x/7

Simple and best practice solution for (2x/7)-7=-x/7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x/7)-7=-x/7 equation:



(2x/7)-7=-x/7
We move all terms to the left:
(2x/7)-7-(-x/7)=0
We add all the numbers together, and all the variables
(+2x/7)-(-x/7)-7=0
We get rid of parentheses
2x/7+x/7-7=0
We multiply all the terms by the denominator
2x+x-7*7=0
We add all the numbers together, and all the variables
3x-49=0
We move all terms containing x to the left, all other terms to the right
3x=49
x=49/3
x=16+1/3

See similar equations:

| 5p^2+10p=46 | | 6x+6÷5=2x-5 | | 1-2m+21=0 | | 4x+5=x+26# | | (4x+3)12=3x-1 | | √x+27=x-3 | | 7x-10=3/5 | | 6q+3q-q=24. | | 3x+4.5=5x | | (2x-10)+50+x=180 | | 12+4x=x-40 | | 18=18+(40+2f/44+f) | | 8x+65=5-2x | | x-8+7=34 | | 8x+7=2+3x | | -1/2(k+1/32)+3/4=k/6-3/4(k-1) | | 4x-8=11-16x | | 12=3-3÷4a= | | -0.3k+2.1=0.4k= | | 2x+x=5x-30 | | 25x^2-50x=-16 | | 11x+5=4x-14 | | -8+n=5n÷4 | | 13x+7=-9-3x= | | 1/3x+1/4=2x-17 | | 3-4h=10 | | X-(2×y)+669=0 | | X-2y+669=0 | | (2.7)^(0.3x)=9 | | (m+8)(m-2)=-15 | | 0.4+3.6/x=1 | | √(2x-9)+√x-6=0 |

Equations solver categories